Pengaruh Islamic Branding, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Kosmetik Wardah pada Remaja Muslimah di Pekanbaru - Fitriani, Fitriani (Jurnal Rumpun Ilmu Ekonomi, 2024)
The purpose of this study is to determine the influence of Islamic branding, price perception and product quality on the decision to purchase wardah cosmetics. To obtain data from these variables, it was taken from the results of the research in the form of distributing questionnaires to respondents spread across Pekanbaru. The subjects of this study are Muslim women, as many as 100. Meanwhile, sampling was used using the taro yamane formula. The data collection method uses observation, interview, questionnaire and documentation methods. Data analysis uses multiple regression analysis. From the results of the study using the determination coefficient test (R2), the results of 92.5% Islamic branding were obtained, the perception of price and product quality together affected the decision to purchase wardah cosmetics, while the remaining 7.5% influenced by other variables that were not studied in this study. From the results of the multiple linear regression test, the results of the study were obtained Y = -3.037 + 0.006 X1 + 0.150 X2 + 0.615 X3 + e, based on the results of the t test (partial) for the Islamic branding variable obtained a sig level of 0.312, then Ho was accepted and H1 was rejected so that it can be concluded that Islamic branding has no effect on the purchase decision, The price perception variable was obtained at a sig level of 0.001 < 0.05, then Ho was rejected and H1 was accepted, so it can be concluded that price perception has a positive and significant effect on the decision to purchase Wardah cosmetics, the product quality variable is obtained at a sig level of 0.001 < 0.05, then Ho is rejected and Ha is accepted, so it can be concluded that product quality has a positive and significant effect on the decision to purchase Wardah cosmetics. And from the f-test (simultaneous) obtained a sig level of 0.001 < 0.05 so it can be concluded that Islamic branding, price perception and product quality simultaneously have an influence on the decision to buy wardah cosmetics in Muslim women in Pekanbaru.